Attiecības ar lietām: Latvijas labdarības veikalu gadījuma analīze - Shirokova, Maria (Latvijas Universitāte, 2022)
Šajā maģistra darbā tika pētītas cilvēku un materiālo lietu attiecības izmantojot Latvijā esošo labdarības veikalu tīkla “Otra Elpa ” gadījuma analīzi. Par galveno pētniecisko jautājumu tika izvirzīts: kādi ir biežāk sastopamākie attiecību veidi starp cilvēkiem un to vai kāda cita izmantotām materiālām mantām. Lai atbildētu uz pētniecisko jautājumu, darba ietvaros tika apzināta esošā literatūra, veiktas aptaujas un intervijas, lai noskaidrotu kādi ir biežāk sastopamākie iemesli, domas un apeja ar materiālām lietām, kuras tie ziedo vai iegādājas “Otra Elpa” labdarības veikalu tīklā. Ar attiecībām starp cilvēku un materiālām lietām šī darba ietvaros tiek saprasts plašs īpašību kopums, kuru cilvēks ir devis lietām. Šajā kopumā ietilpst emocionālā piesaiste, īpašnieka attieksme, lietu stāvoklis, kā arī izmantošanas un piederības pazīmes. Šī pētijuma gaitā tika apzināti un analizēti pieejamie zinātniski pētnieciskie resursi par dāvināšanu, ziedošanu, labdarības un lietoto preču veikaliem. Darba noslēgumā tika secināts par ievāktiem datiem un cilvēku un materiālo lietu attiecību izpausmēm, kā arī noskaidroti biežāk sastopamākie cilvēku un materiālo lietu attiecību veidi: kā un kāpēc cilvēki izvēlās ziedot un iegādāties no labdarības veikaliem, mantu lietojuma un piederības pazīmes u.c. Pētījums tika papildināts arī ar “Otra Elpa” veikalu tīkla darbinieku ilustrācijām, kurās ir redzamas mantas un to unikālās lietojuma pazīmes un stāvoklis.

This research paper focuses on the relationships between people and material things with a case study of a chain of “Otra Elpa” charity shops in Latvia . The main research question in this thesis is: what are the most common types of relationships people have with material things they have used or that were used by someone else. The main aim thus was to collect evidence on relationships between people and things they donate or things they buy through the analysis of available literature, surveys, and interviews to identify the most common types of relationships between people and material things and understand why people choose to donate and buy from “Otra Elpa” charity shops and how people care and think about material things they have or had in past. Relationship with things in this research is described as a wider number of characteristics a person gives to things that had already been used by this person previously and subsequently donated (or in some cases, when donation was not made according to some personal reasons). Such characteristics could include different emotional anchors, ways of caring about a particular thing, leaving marks of ownership. It also could include a person's attitude concerning the thing such as evidence of previous usage and care, condition of things, evidence of possessions of previous owner. Specific theoretical resources on the topic of gift-giving, second hands, and charity shops functioning were analyzed and applied in this research. As a result of this research, data about different aspects of relationships were gathered and the most common relationship types were established: how and why people donate and buy things in charity shops, handling of items before donating and after purchase, matters of the emotional connection with previous owners and the aspects of possession - determination when one can say the item is now their own or no more belongs to them. In addition, from the insight of the workers (workers) illustrations of previous possession and traces of previous ownership were collected to contribute to the fuller picture.
Relationships with things: the Case study of Latvian charity shops
Keywords: Antropoloģija; charity shops; donations; relationships with things; previous ownership; biographies of things